2020
DOI: 10.21873/invivo.12210
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mortality and Left Ventricular Ejection Fraction in Patients With Takotsubo Syndrome Versus Acute Coronary Syndrome

Abstract: Background/Aim: The association between ejection fraction (EF) and mortality in TTS patients as compared to ACS is limited. This study aims to investigate the association between EF and clinical outcomes in patients with TTS as compared to ACS. Patients and Methods: This study compared in-hospital, and long-term incidence of clinical outcomes for 5 years in patients with TTS and ACS. The study was composed of two groups EF≥35% and EF<35%. Results: The long-term mortality of the EF≥35% for 5 years was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Citro et al ( 30 ) found that patients in the LVEF ≤35 group were older than those in the LVEF >35 group and were more likely to have adverse cardiovascular events. Abumayyaleh et al ( 31 ) found that after 5 years of follow-up, the long-term mortality of TTS patients was significantly higher than that of ACS patients. In a study of abnormal left ventricular wall motion and coronary artery flow, it was found that during the acute phase of TTS, the myocardial blood flow of the dysfunctional left ventricular segment was lower than that of the normal ventricular wall motion ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Citro et al ( 30 ) found that patients in the LVEF ≤35 group were older than those in the LVEF >35 group and were more likely to have adverse cardiovascular events. Abumayyaleh et al ( 31 ) found that after 5 years of follow-up, the long-term mortality of TTS patients was significantly higher than that of ACS patients. In a study of abnormal left ventricular wall motion and coronary artery flow, it was found that during the acute phase of TTS, the myocardial blood flow of the dysfunctional left ventricular segment was lower than that of the normal ventricular wall motion ( 32 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cardiogenic shock precipitates the acute disease in approximately 20% of TTS and 6–10% of STEMI [ 4 , 48 ]. There is no unanimous consensus about the best strategy to treat cardiogenic shock in TTS, but previous studies showed that TTS patients are more likely to require mechanical respiratory support than ACS [ 49 ]. Notwithstanding, the mortality rate is substantially higher among cardiogenic shock due to STEMI ( 50%) vs TTS (15%) [ 39 , 50 ].…”
Section: In-hospital Outcomesmentioning
confidence: 99%